Planes have wings and other questions about transportation - Maynard, Chris (New York : Kingfisher Books, 1993)
This book answers questions about transportation and vehicles, including "Do airships run on air?" and "Why don't ships sink?"
Includes index.
4-8
Keywords: Transportation; Vehicles; Questions and answers